An M/ G/1 queue with two phases of service subject to the server breakdown and delayed repair - Choudhury, Gautam; Tadj, Lotfi (Applied mathematical modelling, 2009)
This paper deals with the steady-state behaviour of an M/ G/1 queue with an additional second phase of optional service subject to breakdowns occurring randomly at any instant while serving the customers and delayed repair. This model generalizes both the classical M/ G/1 queue subject to random breakdown and delayed repair as well as M/ G/1 queue with second optional service and server breakdowns. For this model, we first derive the joint distributions of state of the server and queue size, which is one of chief objectives of the paper. Secondly, we derive the probability generating function of the stationary queue size distribution at a departure epoch as a classical generalization of Pollaczek–Khinchin formula. Next, we derive Laplace Stieltjes transform of busy period distribution and waiting time distribution. Finally, we obtain some important performance measures and reliability indices of this model.